Collective Bargaining, Mutuality, and Workers Participation in Management: An International Analysis - Derber, Milton (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1980)
Since the end of World War II, worker participation in management has expanded in varying degrees, in different forms, and at different levels. In West Europe both collective bargaining and mutualism have expanded dramatically and workers participation in management seems destined to advance. In Britain and North America the adversary System of collective bargaining has predominated. Mutualistic schemes have been in the small minority. The attitudinal climate has not been conducive to consensus thinking in industrial relations.